Appendiceal mucocele - a radiologists view - Válek, V; Bartušek, D; Svoboda, M; Válek, V; Procházka, V (Rozhledy v chirurgii, 2021)
Appendiceal mucocele is an obstructive dilatation of the appendix, which results from the filling of its lumen with mucus. This is a rare condition that is asymptomatic in half of the patients. Its severity depends on the cause of appendiceal dilatation. In a small percentage of cases, the dilated appendix ruptures, leading to the development of serious complication; this is termed as pseudomyxoma peritonei. Due to the possibility of malignant etiology of the mucocele, surgical resection remains an essential part of the treatment.
Keywords: Mucocele; Appendix; nádory apendixu; Appendiceal Neoplasms; Radiologists; apendix; ultrasonography − computed tomography; Humans; Pseudomyxoma Peritonei; peritoneální nádory; Peritoneal Neoplasms; lidé; pseudomyxom peritonea; appendiceal mucocele − pseudomyxoma peritonei − appendiceal mucinous neoplasm; mukokéla; radiologové